2023
DOI: 10.3390/cancers15164040
|View full text |Cite
|
Sign up to set email alerts
|

Adequate Pelvic Lymph Node Dissection in Radical Cystectomy in the Era of Neoadjuvant Chemotherapy: A Meta-Analysis and Systematic Review

Abstract: Radical cystectomy (RC) with pelvic lymphadenectomy (PLND) serves as the gold-standard treatment for muscle-invasive bladder cancer (MIBC). Numerous studies have shown that the number of lymph nodes (LN) removed during RC could affect patient prognosis. However, these studies confirmed the association between PLND and survival outcomes prior to the widespread adoption of neoadjuvant chemotherapy (NAC). Consequently, this study aimed to investigate the prognostic role of PLND in patients previously pretreated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Four patients were treated with NAC. As shown in a recent meta‐analysis, the prognostic benefit of extended lymphadenectomy in terms of eradication of lymphonodular micrometastases could be reversed by such treatment 5 . Although detection of lymph node metastases is not the main goal of our work, this still has the potential to influence our results.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Four patients were treated with NAC. As shown in a recent meta‐analysis, the prognostic benefit of extended lymphadenectomy in terms of eradication of lymphonodular micrometastases could be reversed by such treatment 5 . Although detection of lymph node metastases is not the main goal of our work, this still has the potential to influence our results.…”
Section: Discussionmentioning
confidence: 90%
“…ePLND represents an integral part of radical cystectomy in MIBC as it defines adjuvant treatment needs and serves as a diagnostic tool to assess patient's prognosis 3 . It is unclear whether the extension of the standard PLND template leads to a prognostic improvement, 4,5 especially when neoadjuvant chemotherapy was performed. The LEA trial, indicated a 3%–8% occurrence of PLND‐related complications such as lymphocele and lymphedema 6 .…”
Section: Introductionmentioning
confidence: 99%
“…37 More recent observational and cohort studies have varying results with several showing no benefit, but in those that did report an advantage with a more extensive LND, this advantage was noted in patients who had not received NAC. [38][39][40][41] The largest observational study (n [ 19,020) using SEER data did report statistically significant associations between the extent of pelvic LND and cancerspecific mortality (HR [ 0.99; P < .001) and rates of lymph node invasion (OR [ 1.01; P [ .001) in a mixed population of patients with MIBC and NMIBC; however, the effect sizes were very small. 41…”
Section: Pelvic Lymphadenectomymentioning
confidence: 99%
“…reported only a 15% local response rate in patients with cN+ [7]. Some researchers have argued that the count of excised LNs significantly influences the long-term oncological outcomes in patients with cN+ treated with induction chemotherapy [7,8], whereas the merits of extended pelvic lymph node dissection (PLND) remain debated for patients treated with NAC [9]. Consequently, the oncological outcomes for patients with pathologically verified LNs post-induction chemotherapy may not mirror those post-NAC.…”
Section: Introductionmentioning
confidence: 99%